The Period of Development of Khorazm's Charitable Traditions - Sabirova Nasiba Ergashevna (Research Parks Publishing LLC, 2024)
This article discusses the latest developments in the art of giving. Also, the parikhan-porkhans scattered in Khorezm are a form of shamans, and shamanism is considered to be one of the first stages in the formation of the art of Bakhshi, and the professions of medicine and sorcery were synthesized in the Bakhshi, who were masters of music and words, even Ergash Jumanbulbul information was given that his son also performed the role of